The Dual Impact of Blockchain Adoption: Enhancing Financial Performance and Microeconomic Stability with Emerging Challenges - Putra P, Komang Widhya Sedana; Lasmi, Ni Wayan (Jurnal Manajemen Bisnis, 2025)
Research aims: This study examines the impact of blockchain adoption on the microeconomic stability of micro, small, and medium enterprises (MSMEs), with financial performance and access to financial services as mediating variables.Design/Methodology/Approach: The analysis employed Partial Least Squares Structural Equation Modeling (PLS-SEM) using data from 200 MSME owners in Indonesia who have integrated blockchain technology into their operations. The constructs, blockchain adoption, financial performance, access to financial services, and microeconomic stability, were measured through a structured questionnaire based on validated indicators from prior research.Research findings: The findings reveal that blockchain adoption significantly enhances financial performance and microeconomic stability. Financial performance strengthens the direct effect of blockchain adoption on stability, while access to financial services positively mediates the relationship between blockchain use and economic stability. Interestingly, an adverse indirect effect through financial performance was observed, suggesting potential implementation-related or contextual risks that merit further investigation.Theoretical Contribution/Originality: This research comprehensively explains MSMEs' blockchain adoption behavior and economic implications by integrating the Technology Acceptance Model (TAM) and the Resource-Based View (RBV) framework.Practitioners/Policy Implications: To promote inclusive adoption, policymakers and MSME stakeholders should prioritize secure and user-friendly blockchain systems, expand access to digital financial services, and develop adaptive regulatory frameworks. Strategic adoption should weigh both efficiency gains and potential challenges, including systemic risks, technological volatility, and unequal benefit distribution.Research Limitations/Implications: The study's scope is limited to MSMEs in Indonesia; future research should explore cross-regional and sectoral comparisons, long-term impacts, regulatory variations, and adoption dynamics across diverse contexts.